Successful conservative management of myiasis of an episiotomy wound and the uterine cavity postnatally: A case report - Satyala Satya Priya; Singuang Kamei Gaithaoliu; Kim Johanna Catharina Verschueren; Parishuddharao Koduri (Case Reports in Women's Health)
Myiasis refers to an infestation by maggots or fly larvae. Urogenital myiasis, particularly in the uterine cavity, is extremely rare. Previously reported cases involved uterine prolapses, typically managed with hysterectomy. We describe the successful conservative management of myiasis in an episiotomy wound with extension into the uterine cavity. The case involved a woman in her 30s who gave birth to her third child eight days prior and presented with a painful and infected episiotomy site with “worms” emerging from her vagina. Her poverty had led to her malnourishment and poor hygiene; she was being treated for pulmonary tuberculosis. She required 11 days of inpatient care, which included broad-spectrum antibiotics, a three- to five-day course of ivermectin, clindamycin and albendazole, larvae extraction, manual vacuum aspiration, uterine cavity irrigation and the daily application of a menstrual pad soaked in turpentine oil. No further maggots were detected near the end of her hospital stay, nor at follow-up. This case demonstrates that conservative treatment can be effective, though it requires patience. Ensuring proper nutritional status and personal hygiene in the postpartum period is critical to preventing wound infections complicated by myiasis.